The Framework of Person-Centredness across Human Services (FPCHS): An evidence-based framework for practice - Waters, Rebecca (2019)
The term “person-centred” is increasingly used in human services to define desirable approaches to service delivery. There is, however, no consensus in the literature about the principles of person-centredness and its constituent characteristics, although contemporary government policies regarding service delivery for various groups of vulnerable people have been developed with this approach in mind. By drawing on the literature and the views of an expert reference group, this research-informed presentation introduces a descriptive framework of person-centred principles and constituent characteristics as they apply to people with disability, elders and people with mental health issues. Given the major social policy reforms in Australian disability, aged care and mental health service delivery, the results may inform social work education, practice, and research by providing a framework for response in these human services.